3D printing collagen/chitosan scaffold ameliorated axon regeneration and neurological recovery after spinal cord injury. Issue 9 (14th April 2019) - Sun, Yan; Yang, Cheng; Zhu, Xu; Wang, Jing‐Jing; Liu, Xiao‐Yin; Yang, Xi‐Ping; An, Xing‐Wei; Liang, Jun; Dong, Hua‐Jiang; Jiang, Wei; Chen, Chong; Wang, Zhen‐Guo; et al.
Abstract: Spinal cord injury (SCI) is a disaster that can cause severe motor, sensory, and functional disorders. Implanting biomaterials have been regarded as hopeful strategies to restore neurological function. However, no optimized scaffold has been available. In this study, a novel 3D printing technology was used to fabricate the scaffold with designed structure. The composite biomaterials of collagen and chitosan were also adopted to balance both compatibility and strength. Female Sprague–Dawley rats were subjected to a T8 complete‐transection SCI model. Scaffolds of C/C (collagen/chitosan scaffold with freeze‐drying technology) or 3D‐C/C (collagen/chitosan scaffold with 3D printing technology) were implanted into the lesion. Compared with SCI or C/C group, 3D‐C/C implants significantly promoted locomotor function with the elevation in Basso–Beattie–Bresnahan (BBB) score and angle of inclined plane. Decreased latency and increased amplitude were observed both in motor‐evoked potential and somatosensory‐evoked potential in 3D‐C/C group compared with SCI or C/C group, which further demonstrated the improvement of neurological recovery. Fiber tracking of diffusion tensor imaging (DTI) showed the most fibers traversing the lesion in 3D‐C/C group. Meanwhile, we observed that the correlations between the locomotor (BBB score or angle of inclined plane) and the DTI parameters (fractional anisotropy values) were positive. Although C/C implants markedly enhanced biotin dextran amine (BDA)‐positive neural profiles compared with SCI group, rats implanted with 3D‐C/C scaffold displayed the largest degree of BDA profiles regeneration. Collectively, our 3D‐C/C scaffolds demonstrated significant therapeutic effects on rat complete‐transected spinal cord model, which provides a promising and innovative therapeutic approach for SCI. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 1898–1908, 2019.